2008
DOI: 10.4067/s0716-97602008000100007
|View full text |Cite
|
Sign up to set email alerts
|

Chronobiologic blood pressure assessment: Maturation of the daily rhythm in newborn foals

Abstract: Circadian rhythmicity of physiological processes in animals has been described for some variables. In order to investigate the daily rhythmicity of blood pressure, seven foals (Equus caballus) were used for 40 days after birth. Measurements of blood pressure were done by means of an oscillometric apparatus (Argus TM-7, Schiller, Barr Switzerland) with the foals in a standing position and the cuff placed around the tail. Blood pressure was recorded twice a day, 1 hour before dawn and 1 hour before dusk for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…The existence of a rhythmic pattern of body temperature, that emerges within the first 10 days of life, and matures fully during the first month after birth, confirm the efficiency of thermal homeostasis mechanisms in the newborn that working perfectly from the very first weeks of life both in foals born within 340 days and those born between 341 and 355 days (Piccione et al 2005a). Different from that observed for the body temperature, blood pressure circadian rhythm was not observed in foals ( Figure 2) monitored for 40 days after birth (Piccione et al 2008a). It is probably due, not only to an incomplete anatomicalfunctional development of the cardiovascular system (Piccione et al 2005a), but also to the immaturity of the autonomic nervous system, that with the circadian fluctuation of endogenous opioids, hypothalamus-hypophysis axis, renin-angiotensin-aldosteron complex, renal function and vasoactive peptides, affects the circadian rhythm of blood pressure (Portaluppi et al 1990(Portaluppi et al , 1992(Portaluppi et al , 1993(Portaluppi et al , 1996.…”
Section: Maturation Of the Biological Clock In Foalscontrasting
confidence: 78%
“…The existence of a rhythmic pattern of body temperature, that emerges within the first 10 days of life, and matures fully during the first month after birth, confirm the efficiency of thermal homeostasis mechanisms in the newborn that working perfectly from the very first weeks of life both in foals born within 340 days and those born between 341 and 355 days (Piccione et al 2005a). Different from that observed for the body temperature, blood pressure circadian rhythm was not observed in foals ( Figure 2) monitored for 40 days after birth (Piccione et al 2008a). It is probably due, not only to an incomplete anatomicalfunctional development of the cardiovascular system (Piccione et al 2005a), but also to the immaturity of the autonomic nervous system, that with the circadian fluctuation of endogenous opioids, hypothalamus-hypophysis axis, renin-angiotensin-aldosteron complex, renal function and vasoactive peptides, affects the circadian rhythm of blood pressure (Portaluppi et al 1990(Portaluppi et al , 1992(Portaluppi et al , 1993(Portaluppi et al , 1996.…”
Section: Maturation Of the Biological Clock In Foalscontrasting
confidence: 78%
“…Stimulation tests were performed both in the morning and the evening with no effect on the time of day seen in the cortisol responses, which is expected in foals of this age. Foals inherently lack a circadian rhythm until they are 20‐40 days of age, at which point they develop a diurnal rhythm 49,50 …”
Section: Discussionmentioning
confidence: 99%
“…Foals inherently lack a circadian rhythm until they are 20-40 days of age, at which point they develop a diurnal rhythm. 49,50 The objective of this study was to investigate if an AVP stimulation test is an appropriate diagnostic tool to stimulate the HPAA and identify critically ill foals with RAI. We demonstrated that AVP reliably produces a significant HPAA stimulation in neonatal foals, with resulting rise in both cortisol and ACTH, as compared to previously published studies in adult horses.…”
Section: Discussionmentioning
confidence: 99%
“…In kid goats, Piccione et al [100] has reported that the maturity of the circadian rhythm does not mature until the end of the second year of life of the animals. Moreover, 40-day-old foals have blood pressure immaturity [101], a factor that need to be considered when trying to administer caffeine to neonates. Also, caffeine has been shown to alter circadian rhythms in humans and animals [99].…”
Section: Future Directionsmentioning
confidence: 99%